2019
DOI: 10.4103/jwas.jwas_903_19
|View full text |Cite
|
Sign up to set email alerts
|

Testicular cancer at the University of Port Harcourt Teaching Hospital: A 10-year retrospective review

Abstract: Background: Testicular cancers are rare malignancies. They are however very common in males aged 15–40 years. Reports of increasing incidence of testicular cancer in western countries have been noted. Despite the increasing incidence, mortality has remained low in these countries. There are few publications on the management of testicular tumors in Nigeria. Aim: The aim of this study was to determine the hospital prevalence and highlight our experience in the management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Interestingly, the most common indication for LLA in that study was also uncontrolled diabetes mellitus. Similarly, another retrospective review conducted in a Western Cape teaching hospital revealed that LLAs were commonly conducted on elderly females as a consequence of diabetic foot gangrene (Hagan et al 2018 ). In contrast, a recent systematic review of studies investigating gender differences in diabetic-related amputations found that men were more likely to undergo amputations than women (Fan & Wu 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the most common indication for LLA in that study was also uncontrolled diabetes mellitus. Similarly, another retrospective review conducted in a Western Cape teaching hospital revealed that LLAs were commonly conducted on elderly females as a consequence of diabetic foot gangrene (Hagan et al 2018 ). In contrast, a recent systematic review of studies investigating gender differences in diabetic-related amputations found that men were more likely to undergo amputations than women (Fan & Wu 2021 ).…”
Section: Discussionmentioning
confidence: 99%